(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article presents some episodes of popular collective action in the south of Greater Buenos Aires during the last argentinian dic- tatorship based on the analysis of a contentious dynamic that combines forms of religious celebration and popular mobilization in the process of territorial constitution of a catholic diocese. From a topographical history of collective action, it dialogues with studies on argentinian catholicism and popular resistance during the last dictatorship, reconstructs a local repertoire of collective action, describes the network of activisms and traces disputes over space with military and police authorities. Finally, it highlights that a look that integrates place, history and collective action expandr our perception of the experience of the popular classes.